Biosimilar vs originator insulins: Systematic review and meta‐analysis. Issue 7 (17th April 2018) - Yamada, Tomohide; Kamata, Ryuichi; Ishinohachi, Kotomi; Shojima, Nobuhiro; Ananiadou, Sophia; Nom, Hisashi; Yamauchi, Toshimasa; Kadowaki, Takashi
Abstract : Biosimilar insulins have expanded the treatment options for diabetes. We compared the clinical efficacy and safety of biosimilar insulins with those of originator insulins by conducting a meta‐analysis. A random‐effects meta‐analysis was performed on randomized controlled trials comparing biosimilar and originator insulins in adults with diabetes. Studies were obtained by searching electronic databases up to December 2017. Ten trials, in a total of 4935 patients, were assessed (2 trials each on LY2963016, MK‐1293, Mylan's insulin glargine and SAR342434, and 1 trial each on FFP‐112 and Basalog). The meta‐analysis found no differences between long‐acting biosimilar and originator insulins with regard to reduction in glycated haemoglobin at 24 weeks (0.04%, 95% confidence interval [CI] –0.01, 0.08; P for efficacy = .14, I 2 = 0%) or at 52 weeks (0.03%, 95% CI –0.04, 0.1), or reduction in fasting plasma glucose (0.08 mmol/L, 95% CI 0.36, 0.53), hypoglycaemia (odds ratio 0.99, 95% CI 0.96, 1.03), mortality, injection site reactions, insulin antibodies and allergic reactions. Analyses stratified by type of diabetes and prior insulin use yielded similar findings. Similarly, no significant differences were found between short‐acting biosimilar and originator insulins. In summary, our meta‐analysis showed no significant differences in clinical efficacy and safety, including immune reactions, between biosimilar and originator insulins. Biosimilar insulins can increase access to modern insulin therapy and reduce medical costs.